Works of Art in the Turkish Grain Board (TMO) General Directorate Building - Güler Özyıldıran (DEPARCH Journal of Design Planning and Aesthetics Research)
Turkish Grain Board (TMO) General Directorate Building was designed by Vedat Özsan, Cengiz Bektaş ve Oral Vural (Özsan-Bektaş-Vural Architects) in 1964 and constructed between 1964 and 1968 in Ankara. One of the significant aspects of the building is the involvement of works of art. One percent of the building cost was allocated to the works of art. Moreover, the architects get inspired by some artists during the building design. Such kind of art and architecture synthesis was common in modern architecture between 1950 and 1980 both in Turkey and in the world. However, this aspect of the TMO building is not known enough in the literature. The aim of this study is to analyze the works of art in TMO General Directorate building in terms of art and architecture synthesis. The research method was mainly based on the literature about art and architecture synthesis, individual writings of architect Cengiz Bektaş and some artists (Bedri Rahmi Eyüboğlu, Burhan Alkar etc.) and the analysis of the building on site. These works of art vary from wall ceramic to stained glass, and after 1988, a monumental sculpture was added to the building via competition. Moreover, after this sculptor competition, TMO established a plastic arts application center in 1989.